Study On the Effectiveness of Recruitment Processes at Pt. Kelola Lingkungan Kita - Hanut Priyanto; Tantri Yanuar Rahmat Syah; Rhian Indradewa; Diana Fajarwati (Journal of Multidisciplinary Academic, 2020)
The first stage prior to the selection process is employee recruitment, then continues to the placement of candidates. The right hiring employee candidates over company is the most important part of the venture. An effective recruitment process can be reducing turnover of company. The interviews process and background checks are ensuring that the company will hire reliable candidates and carry out the company's planned goals of providing quality service to customers. There are several factors that affect the effectiveness of the recruitment process at PT. KELOLA LINGKUNGAN KITA (KLK) which is have a consists of cost per person employee candidate, volume of applicants, time to fill in, quality of recruitment, tenure, and employee attitude. This study aims to review the most effective way of recruiting employees in order to obtain competent employees. In this study, we use a qualitative method that will describe the topic and explain the results of the interview. The purpose of this study was to determine how effective the recruitment process at PT. KLK. The result of this research is that the recruitment process of PT. KLK is effective, but it is important to maintain the recruitment process in the company, because the recruitment process is the first stage in deciding whether a company has good employees or not.